Pengaruh Kepuasan Penggunaan Mobile Banking terhadap Loyalitas Nasabah di Kota Sampit - Agustin, Nia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study was conducted with the aim of knowing how the effect of satisfaction of using Mobile Banking on loyalty and also to find out the differences in satisfaction of using Mobile Banking at BNI and BRI Banks with research locations in Sampit City. This research is a type of quantitative research with the population in this study are customers who use Mobile Banking Bank BNI and BRI using a sample technique in the form of purposive sampling with a total of 100 respondents. The results showed that the satisfaction of using Mobile Banking has a significant positive effect on customer loyalty. The results also show that there is no difference in the satisfaction of using Mobile Banking at Bank BNI and Bank BRI.